Special aspects of motivation of the structural subdivisions of the state emergency service of Ukraine in terms of physical self-culture - Stetsenko, A.I.; Arhipenko, V.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to determine the motivation of employees of structural subdivisions of the State Emergency Service of Ukraine to improve their level of professional competence by means of physical training. Material: questionnaire survey of 130 rescue workers aged 25 to 40 years. Results: the main motives of rescue team personnel for physical culture and sports activities are gain in physical health and professional competence, while performing rescue missions. It was established that, when on duty, most of the firefighters and rescue workers are not engaged in physical exercise at all; household chores and poor state of health in case of men prevent rescue team employees from doing exercises outside of working hours. It was found that fire-rescue specialists give preference to the development of muscle strength during professional physical trainings and would like to perform power exercises. Conclusions: the low level of motivation of current fire-rescue workers for physical self-improvement requires optimization of control over professional physical education in departments of the State Emergency Service of Ukraine.